205k views
1 vote
Solve for x.
-3 (x-1) + 8 (x-3) = 6x + 7 - 5x
Pls help as soon as possible thanks! :D

User Lazd
by
6.0k points

1 Answer

2 votes

Answer:

x = 7

Explanation:

-3 (x - 1) + 8 (x - 3) = 6x + 7 - 5x

-3 (x - 1) + 8 (x - 3) = 6x - 5x + 7

-3 (x - 1) + 8 (x - 3) = x + 7

-3x + 3 + 8x - 24 = x + 7

-3x + 8x + 3 - 24 = x + 7

5x - 21 = x + 7

+21 +21

--------------------------------------------------

5x = x + 28

-x -x

---------------------------------------------------

4x = 28

/2 /2

----------------------------------------------------

x = 7

User JoshFinnie
by
6.4k points